A decade of dynamics of residential location, car ownership, activity, travel and land use in the Seattle metropolitan region. (August 2018) - Lee, Jae Hyun; Goulias, Konstadinos G.
Abstract: Using data of attitudes in the Puget Sound region we first identify predispositions in favor of car use (car loving persons and households) and distinguish them from other predispositions favoring other modes (transit and carsharing lovers). Then we explore if like-minded people (homophily) live together and examine heterogeneity within their households. To do this we analyze attitudinal data using multilevel latent class clustering that allows identification of groups of persons and groups of households jointly. Our analysis identifies distinct groups of people with different attitudes towards modes and we do not find strong homophily in attitudes within households. The distinction of attitudes among persons transfers well to the household level giving us the opportunity to identify and test differences among the different attitudinal groups using longitudinal records. We then move to a longitudinal analysis using a small sample of households that participated in more than ten years of the Puget Sound panel survey to explore the sequence of their residential location characteristics, car ownership, and travel. We find in descriptive statistics and in a second application of multilevel cluster models that carpool and transit loyalty persists over time by a portion of car pool and transit lovers. We also find sustained use of cars by car loving households, sustained car use of a neutral in attitudes group, a group of younger households with positive attitudes towards carsharing and sustained car sharing over time, and a possibly disenfranchised older household group lacking access to opportunities. The inclusion in the analysis of the two residential location characteristics (evolution of density and diversity around the household residence) enabled a more complete analysis and a clearer description of household context for both attitudes and behavior.